Effect of Integrated Postharvest Handling Practices on Quality and Shelf Life of Cactus Pear [Opuntia ficus-indica (L.) Mill.] Fruits - Shumye, Getachew; Woldetsadik, Kebede; Fitiwi, Ibrahim (Journal of Postharvest Technology, 2014)
This experiment was conducted to determine the effect of postharvest handling practices on quality and shelf life of cactus pear [Opuntia ficus-indica (L.) Mill.] fruits through integrating postharvest chemical, packaging, and storage treatments. Storage in evaporative cooler (EC) significantly improved all the quality parameters of fruits due to the decrease in mean temperature by 2.81oC and increase of relative humidity by 11% than ambient storage. Packaging maintained fruit quality better than that of non-packaged ones. Similarly, chemical treatments, especially CaCl2 and 2, 4- Dichlorophenoxyacetic acid enabled better retention of physical and chemical quality characteristics of fruits. The combined effects of the treatments resulted in maintenance of lower levels of pH and higher levels of total soluble solids, titratable acidity, ascorbic acid, pulp firmness, as well as marketability of cactus pear fruits. Hence, the shelf life of cactus pear fruits could be extended for two to three weeks with nutritional quality attributes maintained in good condition using combinations of chemicals, packaging fruits in polyethylene sheet and then storing them under EC.